Experiences with Medicaid Renewal and Reauthorization Policies in the Context of Child Health and Vaccine Coverage. Issue 2 (27th January 2022) - Holroyd, Taylor A; Oloko, Oladeji K; Limaye, Rupali J
Abstract: Difficulties complying with Medicaid recertification requirements may be responsible for a portion of Medicaid disenrollments and may impact access to preventive care. This study aimed to explore the barriers parents experienced renewing their child's Medicaid, how those barriers impact access to healthcare, and how changes in Medicaid policy can improve child health outcomes. To understand the barriers associated with Medicaid renewal, authors conducted in-depth interviews ( N  =   24) with racially and demographically diverse parents living in Baltimore. They found that administrative burden, lack of awareness regarding reauthorization, challenges with navigation assistance, and lack of access to the renewal system were crucial barriers to renewing Medicaid. Many participants identified negative impacts on child health outcomes resulting from lapses in coverage, including lack of healthcare access and missed immunizations. Drawing on these findings, the authors provide recommendations for streamlining and clarifying the Medicaid renewal process in Maryland, and the role of social work policy and practice in reducing barriers to renewal.